Forest cover change in Peninsular Malaysia using satellite remote sensing data - Mohd. Najib, Nazarin Ezzaty (2015)
Forest balance the global ecosystem by maintaining sustainable interaction between living and non living things. Deforestation caused land to be fragile, and destroyed water catchment area. Soil will absorb large amount of water and eroded. The water that caught by the forest before flows unhindered to the river with the soil and cause extreme flood. Thus forest change should be monitored to maintain sustainable ecosystem. Sustainable forest management should be done to maintain future forest resources . Forest replantation have been done by forestry department. However, it is not sufficient to balance the ecosystem. Malaysia forest loss has been increased and recorded high rate of deforestation. Thus, continuous forest monitoring should be done.Remote sensing technology with the multispectral image that has high spatial, temporal, and radiometric resolution, possible to monitor the forest cover change in short period of time. The aim of this study is to investigate the forest cover change in Malaysia between 1990 and 2010 using Landsat and ALOS Palsar satellite images. CLASlite software used Landsat data, while ALOS Palsar use threshold to classify forest. Besides, comparison of forest cover from Support Vector Machine and Maximum Likelihood Classifier is carried out. Then the result is validated with Forestry Department statistics. Comparison of total forest cover from CLASlite, ALOS Palsar, land use map and forestry statistics also was being made. The change of forest is detected by selecting Iskandar and Kuala Lumpur area .CLAlite also show the deforestation and disturbance area in Peninsular Malaysia. Results show that a forest loss value is high, compare to forest gain value. Iskandar have forest loss about 54 966 hectare and gain 21 411 hectare, while Kuala Lumpur loss about 2 521 hectare and gain 3 004 hectare of forest. The result of this study will be useful for Forestry Department to monitor the deforestation in Malaysia.